The impact of workdays lost to strikes on wage growth in Turkey - Emre Ünal; Nezir Köse (Journal of Economic Structures, 2018)
This paper empirically examines how wage growth in Turkey has been influenced by workdays lost to strikes, by inflation and by real GDP through the vector autoregression model for the annual period 1963-2015. According to empirical results, wage growth is largely affected by workdays lost to strikes and inflation. This analysis is tested by considering workdays lost to industrial action in order to understand the main dynamics behind wage growth, because this is a significant factor in the elimination of macroeconomic imbalances in the Turkish economy. As a conclusion, the mathematical base social contract, new wage-setting, and inflation policies are recommended to reduce macroeconomic problems in Turkey.
Keywords: C32; C67; E02; J30; J50; 330; Mathematical base social contract; Vector autoregression (VAR); Input-output analysis; Industrial actions; Turkey